ABOVE-GROUND BIOMASS ESTIMATION OF OPUNTIA FICUS-INDICA (L.) MILL. FOR FORAGE CROP IN A MEDITERRANEAN ENVIRONMENT BY USING NON-DESTRUCTIVE METHODS. (13th April 2016) - REIS, CARLOS MANUEL GASPAR; GAZARINI, LUIZ CARLOS; FONSECA, TERESA FIDALGO; RIBEIRO, MARIA MARGARIDA
SUMMARY: In marginal lands Opuntia ficus-indica (OFI) could be used as an alternative fruit and forage crop. The plant vigour and the biomass production were evaluated in Portuguese germplasm (15 individuals from 16 ecotypes) by non-destructive methods, 2 years following planting in a marginal soil and dryland conditions. Two Italian cultivars (Gialla and Bianca) were included in the study for comparison purposes. The biomass production and the plant vigour were estimated by measuring the cladodes number and area, and the fresh (FW) and dry weight (DW) per plant. We selected linear models by using the biometric data from 60 cladodes to predict the cladode area, the FW and the DW per plant. Among ecotypes, significant differences were found in the studied biomass-related parameters and several homogeneous groups were established. Four Portuguese ecotypes had higher biomass production than the others, 3.20 Mg ha −1 on average, a value not significantly different to the improved 'Gialla' cultivar, which averaged 3.87 Mg ha −1 . Those ecotypes could be used to start a breeding program and to deploy material for animal feeding and fruit production.